The Effect of Timing of Surgery in Pituitary Apoplexy on Continuously Valued Visual Acuity - Kelly, Patrick D.; Fernando, Shanik J.; Malenke, Jordan A.; Chandra, Rakesh K.; Turner, Justin H.; Chambless, Lola B. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Pituitary apoplexy is often treated urgently, but this is based on studies which assess vision categorically and dichotomizes the time interval between symptom onset and surgery which may introduce bias in measuring an association between the two.Objective This study was aimed to assess for a relationship between continuously valued surgery delay and visual acuity recovery after pituitary apoplexy.Methods In this retrospective study, all patients presenting with symptomatic pituitary apoplexy between 2004 and 2016 were identified from an institutional database. The primary endpoint was visual acuity improvement, measured as the difference in acuity from the pre- to postoperative period, and measured in Logarithm of the Minimal Angle of Resolution (LogMAR) units. Analysis was performed using continuous values of time delay and visual acuity to assess for an underlying association.Results Thirty-two pituitary apoplexy patients were identified. Visual acuity deficits were reported in 81%. The median visual acuity was 0.35 LogMAR (Snellen's fraction 20/40) preoperatively, and 0.1 (20/25) postoperatively (p < 0.01). The time between symptom onset and surgery was not associated with improvement in visual acuity (p = 0.46). When the time delay and visual outcome were intentionally dichotomized, patients undergoing surgery within 2 days of symptom onset had 0.21 times the odds of a good visual outcome (95% confidence interval [CI]: 0.04–1.05).Conclusion When assessed as continuously valued measures, the time from symptom onset to surgical intervention and the improvement in visual acuity are not associated, although intentional dichotomization of data produced conflicting results.
Keywords: acuity; early; delayed pituitary apoplexy; timing; vision